Do public works investments in watershed rehabilitation and small-scale irrigation improve nutrition and resilience? Evidence from bureau for humanitarian assistance interventions in support of Ethiopia’s productive safety net program - Balana, Bedru; Mekonnen, Dawit Kelemework; Arega, Tiruwork; Ringler, Claudia; Bryan, Elizabeth; Yami, Mastewal; Taffesse, Alemayehu Seyoum; Wondwosen, Abenezer (International Food Policy Research Institute, 2024)
Between 2017 and 2021, the Bureau for Humanitarian Assistance (BHA) of the United States Agency for International Development supported public works in the areas of watershed rehabilitation and small-scale irrigation under Ethiopia’s Productive Safety Net Program (PSNP). The investments aimed to improve food security and nutrition and to increase the resilience capacities of households through improved natural resource systems and asset development. However, there is little evidence about how these water-related investments supported household food security, nutritional outcomes, and resilience. This study used a mixed-methods approach to fill some of these knowledge gaps. Econometric results show that households in BHA intervention areas had smaller food gaps, and this association is statistically significant. Similarly, households that adopted small-scale irrigation and water harvesting techniques on their own plots show significantly better nutritional outcomes than those that did not. The results further suggest that in general the households in BHA areas are more resilient than those in non-BHA woredas. However, higher resilience capacities are associated with agricultural water management on own plots rather than with public works in communal lands. Thus, if household security, nutrition and resilience are key goals of program interventions, then programs need to grow intentionality in developing assets, and particularly irrigation.